Graft failure in allogeneic hematopoietic stem cell recipients: diagnosis and treatment - U. V. Maslikova; N. N. Popova; M. Yu. Drokov; E. G. Khamaganova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
Graft failure is a group of complications after allogeneic hematopoietic stem cell transplantation, which occurs according to different data up to 30%. The group of complications includes primary and secondary graft failure, primary, secondary and transient poor graft function and graft rejection. Diagnostic difficulties consist in the lack of unified diagnostic criteria accepted in the transplantation community and in the dual interpretation of these complications according to the foreign literature. The purpose of this literature review was to identify the most common criteria of different types of graft failure and determine the tactics of diagnosis and treatment. In this review we analyzed data from various literature sources, gave definitions of graft failure and poor graft function. We analyzed the literature data on the methods used to treat these conditions.